The mechanism of sulfate on a nitrate denitrifying anaerobic methane oxidation system. Issue 12 (5th October 2022) - Lou, Juqing; Jin, Hao; Li, Jiaping; Lv, Jiao; Xu, Fan; Wang, Ruyi
Abstract : The effects of sulfate on nitrate-DAMO was studied. The intermediate products of the nitrate-DAMO process were analyzed. The abundance of ANME-2d archaea was greatly affected by sulfate. Abstract : The nitrate-denitrifying anaerobic methane oxidation (nitrate-DAMO) process is a methane anaerobic oxidation coupled denitrification process, in which methane is the only carbon source and nitrate or nitrite is the electron acceptor. Sulfate can coexist with nitrate-DAMO microorganisms in natural water and sewage. In order to find out the effect of sulfate on the nitrate-DAMO process, experiments were conducted from the macro to the micro scale. The results showed that the denitrification rate of the nitrate-DAMO system was increased first and then decreased with the increase of sulfate concentration from 0 to 380 mg SO4 2− per L. The nitrate-DAMO system was slightly promoted by the sulfate concentration of 40 mg SO4 2− per L, and the system was inhibited when the sulfate concentration was increased from 80 to 380 mg SO4 2− per L. There was no sulfate consumed in the nitrate-DAMO system, which showed that no sulfate reduction coupled methane anaerobic oxidation occurred during the tests. The production and consumption of methanol were not significantly affected by 40 mg SO4 2− per L sulfate, but when the sulfate was increased to 80 mg SO4 2− per L, the methanol concentration decreased. SEM results showed that the nitrate-DAMO microorganisms produced more extracellular polymeric substances (EPS) to promote the accumulation of individual cells under sulfate stress. Quantitative polymerase chain reaction analysis showed that the ANME-2d gene abundance increased by 100.01% under the influence of 40 mg SO4 2− per L sulfate compared with the control group and decreased by 50.41% under the influence of 80 mg SO4 2− per L sulfate. Then, the pmoA gene abundance increased by 14.50% under the influence of 40 mg SO4 2− per L sulfate compared with the control group and decreased by 21.67% under the influence of 80 mg SO4 2− per L sulfate.